Estuary Clean Up dalam Mendukung Pengelolaan Kawasan Pesisir Desa Sungai Nibung Kalimantan Barat - Mega Sari Juane Sofiana; Ikha Safitri; Syarif Irwan Nurdiansyah (Indonesian Journal Publisher, 2024)
Desa Sungai Nibung is a coastal with high biodiversity, so this village has been designated as a conservation area in West Kalimantan with the main conservation target is mangrove. The mangrove ecosystem has an important ecological role, namely as a habitat for marine and coastal biota. A maintained ecosystem will protect the survival of the biota within it. Therefore, managing coastal areas is essential and a shared responsibility. One of the challenges faced in the management process in Desa Sungai Nibung is plastic waste pollution. This waste comes from disposal and runoff from land, which can enter rivers and the sea. Plastic pollution also comes from fishing activities, such as ship traffic, responsive fisheries, and cultivation. This waste needs to be appropriately managed because there is no final waste disposal site (TPA). Household waste and waste from several shops (plastic food and drink packaging) are dumped directly around the building. The accumulation of plastic waste will continue to increase. Therefore, cleanup activities were carried out to reduce plastic waste. Apart from that, this activity aims to educate activity participants about the negative impact of plastic waste on the environment. This community service activity was carried out by a lecturer in Marine Science, FMIPA, Tanjungpura University, who involved students from the Merdeka Belajar Kampus Merdeka (MBKM) program. Beaches and coastal clean-up from macroplastic waste are carried out in residential areas, docks, and areas near fishing activities and ecotourism areas. Implementation of PKM activities consists of permission and coordination, implementation, monitoring, and evaluation. The waste from activities varies from plastic bags, sachet packaging, and food containers to fishing lines. Plastic waste dominates compared to other waste. Participants' understanding concerning plastic waste pollution and its negative impact on the environment and aquatic organisms increased after the activity took place.